(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This paper explained the result of the opinion and understanding of honour killing among Haryana people. Data is collected from two set of questionnaires one is the locality of the Haryana and other are expert incorporated lawyer, judges, social workers, and others respondents from Haryana. Questionnaire were floated among people by filling 300 target but 250 questionnaires were filled significantly without any missing response. Moreover, 50 responses were collected from the expert category. This research paper based on two sections, in first section general opinion and understanding of honour killing in Haryana is explored, in the second section expert opinions are being recorded in reference of existing and fact of honour killing.